2014
DOI: 10.1016/j.bbamem.2014.06.012
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the C-terminal amidation of mastoparans on their biological actions and interactions with membrane-mimetic systems

Abstract: Polycationic peptides may present their C-termini in either amidated or acidic form; however, the effects of these conformations on the mechanisms of interaction with the membranes in general were not properly investigated up to now. Protonectarina-MP mastoparan with an either amidated or acidic C-terminus was utilized to study their interactions with anionic and zwitterionic vesicles, using measurements of dye leakage and a combination of H/D exchange and mass spectrometry to monitor peptide-membrane interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 47 publications
4
46
1
1
Order By: Relevance
“…From the structural point of view, the C-terminus amidation was shown by NMR to provide an extra hydrogen bonding in Eumenine mastoparan-AF (EMP-AF-NH 2 ) compared with the non-amidated analog (Sforça et al 2004). Similar observations were carried out for Protonectarina-MP using hydrogen deuterium exchange and mass spectrometry (da Silva et al 2014). This helical stabilizing effect was also observed in the less frequent post-translational modification in the N-terminus, for instance its acetylation.…”
Section: Charge Effect On the Affinity And Lytic Activity Of Peptidessupporting
confidence: 56%
“…From the structural point of view, the C-terminus amidation was shown by NMR to provide an extra hydrogen bonding in Eumenine mastoparan-AF (EMP-AF-NH 2 ) compared with the non-amidated analog (Sforça et al 2004). Similar observations were carried out for Protonectarina-MP using hydrogen deuterium exchange and mass spectrometry (da Silva et al 2014). This helical stabilizing effect was also observed in the less frequent post-translational modification in the N-terminus, for instance its acetylation.…”
Section: Charge Effect On the Affinity And Lytic Activity Of Peptidessupporting
confidence: 56%
“…Therefore, the differences in Mastoparan-mediated membrane lysis as well as increased propensity to adopt the active conformation of the peptide might thus explain why C-terminal amidation alters both potency as well as the mechanism of Mastoparan-mediated cytotoxicity. Consistent with this, da Silva et al recently found that C-terminal amidation of related but distinct Mastoparans promoted deeper peptide-membrane interactions[23]. …”
Section: Discussionmentioning
confidence: 57%
“…Previously, C-terminal amidation of PMAP-23 was reported to possess more rapid bactericidal kinetics and more helical structure of it in the bacterial membrane environment than the same concentration of PMAP-23C because of the increased cationic charge (Kim et al, 2011). In addition, the amidation of C-terminal residue might be responsible for the stabilization of the secondary helical structure of mastoparans that is richer than its congener (da Silva et al, 2014). Meanwhile, Irazazabal et al (2016) suggested that the increase of net charge by +1 of [I 5 , R 8 ] MP-amide might compensate and overcome the lower level of coil-to-α-helix transition compared with the non-amidated peptide.…”
Section: Discussionmentioning
confidence: 99%